A genre and multimodal analysis of milk formula advertisements in a local parenting magazine / Lee Yong Yong - Lee , Yong Yong (2017)

(untitled)
There is a recent upsurge in the sales of milk formula today especially with the rise of women participation in the workforce. The global milk formula industry is said to be of worth US$50 billion (£31 billion). As a result, advertisers and milk formula companies face stiff competitions to produce the most effective advertising campaigns. Milk formula companies and advertisers compete to set themselves apart by creating different strategies to promote and sell their products. It is hence interesting to examine how advertisers communicate to potential consumers to buy the milk formula products. This study examines the rhetorical structure of milk formula advertisements in a local parenting magazine, ‘Parenthood’. The purpose of this study is to identify the rhetorical structure besides recognising the communicative purposes of the advertisements. The compositional meaning of advertisements in terms of salience, framing and information value are also looked into. This study adopts the nine-move framework by Kathpalia (1992) to analyse the moves in the data collected. Bhatia’s (1993) framework on communicative purposes and Kress and van Leeuwen’s (1996, 2006) model on multimodal analysis are also adopted to look at the multimodal features used in the advertisements. Thirty five milk formula advertisements have been collected and each move used by the advertisers has been analysed and recorded. Moves with a frequency occurrence of more than 60% are considered as obligatory. Out of nine moves from Kathpalia’s framework, six moves are obligatory. These moves are attracting attention (headlines), targeting the market, justifying the product, appraising the product, establishing credentials and soliciting response. The three remaining moves are considered optional. These moves are providing celebrity and typical user endorsement, offering incentives and using pressure tactics. One new move has been discovered from iv the analysis of the milk formula advertisements. This move is providing footnote or reference. The main communicative purpose of milk formula advertisements has been found to be persuasive. This is achieved by persuading and offering appraisals of the products. As for the multimodal component, the findings revealed that the vertical layout is mostly used and salience is achieved through headlines displayed in the biggest font size along with images used in the most dominant size placed in the background. As for framing, milk formula advertisements apply strict colour contrast to differentiate the set of information. The layout used coincides with the salience and framing of the information made obvious through colour contrast, images and headlines emphasized in size. In order to gain more contextual understanding on milk formula advertisements, an online questionnaire was distributed to parents in Malaysia. Interviews conducted with a copywriter, paediatrician, parents and also a former manager of a milk formula company has also provided further contextual understanding. The different strategies adopted by the advertisers in milk formula advertisements have finally concluded that advertisers’ main intention is to persuade consumers to buy milk formula products. This study enhances knowledge and understanding specifically in the area of genre analysis and multimodality.